PENINGKATAN KETERAMPILAN MENULIS LAPORAN ILMIAH MELALUI METODE PROJECT BASED LEARNING DI PERGURUAN TINGGI - Utomo, Widya Tri; Prasetyo, Danang (Jurnal Edukasi Khatulistiwa : Pembelajaran Bahasa dan Sastra Indonesia, 2020)
The objectives of this study are: 1) to improve the quality of student learning in semester 1 of Ambarrukmo Tourism College Yogyakarta through the Project Based Learning method. 2) to improve the writing skills of semester 1 students report at Ambarrukmo Tourism College Yogyakarta through the Project Based Learning method. This research is a classroom action research conducted in two cycles. Each cycle consists of four stages: (1) planning, (2) implementation phase, (3) observation phase, and (4) analysis and reflection phase. Data collection techniques include interviews, observation, tests, and document analysis. Data were analyzed using comparative and critical descriptive analysis techniques. in the first cycle the number of students who reached 76 was 51% and the average value was 72.3. In the second cycle, after the test writing report the first semester students who passed the study reached 98%. Learning increased by 57%. The average value achieved in the second cycle increased to 83.4. This is an increase of 11.1. The results showed that the application of the Project Based Learning method could improve the quality of learning and report writing skills through the Project Based Learning method in the first semester students of Yogyakarta Ambarrukmo College of Tourism.